Polish Independent Press Summary, no. 72 (1990) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
A digest of Polish underground press (including articles, tables of content, and book covers) compiled by members of the RFE Polish Underground Publications Unit to be used in a daily 20-minute broadcast on Polish samizdat. Extract from Przegląd Wiadmości Agencyjnych, no. 217 (8 December 1989). Extract from Przegląd Wiadmości Agencyjnych, no. 219 (22 December 1989). Extract from Orientacja na Prawo, no. 53 (November 1989). Extract from Obieg bez Cenzury, no. 2 (November 1989). Cover Page from Kis, Jànos. Węgry 1956-57: Czas odbudowy systemu. Warszawa: Niezależna Oficyna Wydawnicza, 1989. Cover Page from Szpotański, Janusz. Towarzysz Szmaciak. [Warszawa]: Myśl, 1989. Cover Page from Mićunović, Veljko. Dziennik Moskiewski - 1956. Warszawa: Niezależna Oficyna Wydawnicza, 1988. Cover Page from Carnegie, Andrzej. Jak Zostać Bogatym? [S.l.]: Sukces, 1988. Cover Page from Carrère d'Encausse, Hélène. Wielkie Urągowisko: Bolszewicy i narody 1917-1930. Warszawa: Most, 1989. Cover Page from Johnson, Paul. Historia Polityczna Świata od Lat Dwudziestych do Osiemdziesiątych. Warszawa, Wrocław: Wers, 1989. Table of Contents from Gruntorád, Jiří. Niezależne Inicjatywy w Czechosłowacji. Warszawa: Wydaw. Grup Oporu Solidarni, 1989.